Comparison of Preferences and Risk Levels of Shallot (Allium ascallonicum L.) Farming in the Highlands and Mediumlands - Sri Hindarti; Arief Joko Saputro (Agricultural Science, 2022)
Shallots are one of the horticultural commodities which are the same as other commodities. This study aims to find out the comparison of the level of business risk and farmers' preferences for risk in the highlands represented by Purworejo Village, Ngantang District, Malang Regency and in the medium plains represented by Tawangargo Village, Karangploso District, Malang Regency. This research was determined by purposive sampling using simple random sampling method using 66 samples of shallot farmers. Analysis of the data used is farming analysis, analysis of production factors of cobb-douglass, analysis of coefficient of variation (CV) and Likert scale. Based on the results of this study indicate that the production factors that significantly influence the shallot farming are seeds, NPK fertilizers, ZA fertilizers, and labor. While the level of risk of farming in the highlands, namely Purworejo Village, Ngantang District, Malang Regency, is lower than the level of risk in the Medium plains, namely Tawangargo Village, Karangploso District, Malang Regency. In addition, farmers' preferences for sources of risk in the highlands tend to be more daring to face risks, while the preferences of farmers in the lowlands are more neutral in facing risks.